Asymptomatic COVID-19 re-infection in a Japanese male by elevated half-maximal inhibitory concentration (IC50) of neutralizing antibodies - Inada, Makoto; Ishikane, Masahiro; Terada, Mari; Matsunaga, Akihiro; Maeda, Kenji; Tsuchiya, Kiyoto; Miura, Kenji; Sairenji, Yu; Kinoshita, Noriko; Ujiie, Mugen; Kutsuna, Satoshi; Ishizaka, Yukihito; et al. (Journal of infection and chemotherapy : official journal of the Japan Society of Chemotherapy, 2021)
“Re-infection” with COVID-19 is a growing concern; re-infection cases have reported worldwide. However, the clinical characteristics of SARS-CoV-2 re-infection, including the levels and role of anti-SARS-CoV-2 Spike protein IgG antibodies and the half-maximal concentration (IC50) of neutralizing antibodies remain unknown. Both the epidemiological and clinical information has been collected during two episodes of COVID-19 in a patient. Laboratory results, including RT-PCR, Ct values, anti-SARS-CoV-2 Spike protein IgG antibodies, and the IC50 of neutralizing antibodies levels were analyzed on the patient. The patient was a 58-year-old man who developed moderate COVID-19 pneumonia with oxygen demand (cannula 2 L/min) in the first episode. By day 30, he recuperated and was discharged after testing negative for SARS-CoV-2. After two and a half months, his three family members showed COVID-19 symptoms and tested positive for SARS-CoV-2. He tested positive for SARS-CoV-2 once again and was asymptomatic (the second episode). The IC50 of neutralizing antibodies against SARS-CoV-2 greatly increased from 50.0 μg/mL (after the first episode) to 14.8 μg/mL (after the second episode), and remained strongly reactive (20.1 μl/mL) after 47 days of the second episode. Epidemiological, clinical, and serological analyses confirmed that the patient had re-infection instead of persistent viral shedding from first infection. Our results suggest that SARS-CoV-2 re-infection may manifest as asymptomatic with increased neutralizing antibody levels. Further studies such as the virus characteristics, immunology, and epidemiology on SARS-CoV-2 re-infection are needed.